Penerapan Pengendalian Proses Inventori Kontrol pada Area Top Board - Ardhana, Tangguh Rajasa; Sari, Rianita Puspa (Peneliti.net, 2024)
The increasingly advanced and rapid development of industry in Indonesia forces companies to have effective and targeted strategies. One method that can be used to provide fast and precise production process services is to reduce the costs incurred so that the production process runs smoothly and consumer demands can be met quickly and on time. The research methodology used in this research is the observation method. The results of this research are that the finish good capacity is safe if the material stored in the WM10 or WM6 area is less than 25 lots, almost full if WM6 is filled with 26-34 lots, full if WM6 is more than 34 lots. The best method for WINQB software is SES, stock demand and using a stock buffer of 2%. The Top Board material schedule for 17 days is 4749 with a cumulative total of 4861, a percentage of 102.35%. JIT Implementation Results: The number of stocks per week was 4014 and stock was 103, a percentage of 2.56% and a decrease of 99.44%. It can be concluded that the implementation of the JIT system provides a significant reduction in storage.